Numerical modelling and experimental validation of steel deep drawing processes. Part I: Material characterization - García, Claudio (2006)
This work presents an experimental characterization of the mechanical behaviour of the EK4 deep drawing steel. The experimental procedure encompasses spectrometry, metalography, tension testing and hardness measurements. Special attention is devoted to the derivation of the elastic and plastic parameters involved in the assumed constitutive model based on the anisotropic Hill-48 yield criterion. The simulation of the deformation process during the whole tensile test is subsequently performed with the aim of assessing the adequateness of the proposed methodology. It should be mentioned that the material parameters obtained with this procedure are the basic data for the modelling and experimental validation of different deep drawing applications presented in Part II of this work.